Transformasi Digital Pemasaran Perguruan Tinggi Swasta melalui Artificial Intelligence - Rakhmatullah, M. Waldin (Universitas Tangerang Raya, 2024)
The increasing competition in the higher education sector, particularly among private universities (PTS), demands innovative, technology-driven marketing strategies to attract prospective students. This study explores the implementation of Artificial Intelligence (AI) in marketing management for PTS in Indonesia, focusing on efficiency, personalization, and enhancing the student experience. A quantitative descriptive and exploratory approach was adopted, analyzing data collected through surveys and in-depth interviews with 15 PTS utilizing AI in their marketing strategies. The findings reveal that AI applications, such as chatbots for real-time communication and data analytics to understand prospective students' needs, significantly improve marketing effectiveness. Approximately 73% of PTS reported enhanced responsiveness in communication, while marketing cost efficiency reached an average of 22%. However, challenges such as limited skilled human resources and inadequate technological infrastructure persist. The study underscores the need for investment in staff training and infrastructure development to support broader AI adoption. These findings provide strategic insights for PTS to leverage AI technologies effectively, enhancing their competitiveness in the increasingly dynamic higher education market.